2018
DOI: 10.1111/aor.13335
|View full text |Cite
|
Sign up to set email alerts
|

Radial Artery Tonometry to Monitor Blood Pressure and Hemodynamics in Ambulatory Left Ventricular Assist Device Patients in Comparison With Doppler Ultrasound and Transthoracic Echocardiography: A Pilot Study

Abstract: Noninvasive measurements of blood pressure (BP) and cardiac output (CO) are crucial in the follow-up of continuous-flow left ventricular assist device (CF-LVAD) patients. For our pilot study, we sought to compare BP measurements between a tonometry blood pressure pulse analyzer (BPPA) (DMP-Life, DAEYOMEDI Co., Ltd., Gyeonggi-do, South Korea) and Doppler ultrasound in CF-LVAD patients, as well as to compare the BPPA estimated CO to LVAD calculated blood flow and to the patient's intrinsic CO estimated with tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Furthermore, we utilized the prepared sensors to assemble a pressure sensing array and conducted experiments on detecting human radial artery pulses. The intensity variations of the three-dimensional radial artery pulse wave can be observed very clearly, which is of significant importance for monitoring human health. This work demonstrates that our strategy provides an effective approach for the large-scale fabrication of high-performance flexible pressure sensors.…”
Section: Introductionmentioning
confidence: 80%
“…Furthermore, we utilized the prepared sensors to assemble a pressure sensing array and conducted experiments on detecting human radial artery pulses. The intensity variations of the three-dimensional radial artery pulse wave can be observed very clearly, which is of significant importance for monitoring human health. This work demonstrates that our strategy provides an effective approach for the large-scale fabrication of high-performance flexible pressure sensors.…”
Section: Introductionmentioning
confidence: 80%
“…Recently Alvarez et al published a review on noninvasive blood pressure monitors. 29 They proposed an algorithm with Doppler and automatic blood pressure measurements after reviewing different noninvasive blood devices in multiple studies. Alvarez et al focused mainly on the correlation coefficient of the techniques with the A‐line.…”
Section: Discussionmentioning
confidence: 99%
“…Lin et al showed that in patients undergoing elective neurosurgery, TL-300 system was able to be used for accurate and precise blood pressure monitoring intraoperatively when compared to invasive methods (62). DMP-Life system is another system that uses AT method by using 5 piezoresistive semiconductor transducer sensors after maximal pulse pressure is identified to calculate the SV based on the systolic area of blood pressure waveform and demographic data and has shown to have reasonable accuracy and precision (63,64).…”
Section: Applanation Tonometrymentioning
confidence: 99%